Sulfur-doped ruthenium oxide catalyst as well as preparation method and application thereof
By introducing an appropriate amount of sulfur into the RuO2 catalyst, a sulfur-doped ruthenium oxide catalyst was prepared, which solved the problem of insufficient stability and activity of RuO2 in an acidic environment, and achieved efficient and stable performance in OER reactions.
Patent Information
- Application Number
- CN202411845637.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, RuO2 catalysts have insufficient stability and activity in an acidic environment, making it difficult to quickly and efficiently synthesize high-performance, high-stability sulfur-doped RuO2 catalysts with suitable doping ratios.
By mixing the ruthenium source, sulfur source and alkali metal salt with a solvent, drying and heat treatment, a sulfur-doped ruthenium oxide catalyst was prepared. The doping rate of sulfur was controlled at 0.4 at.%-3 at.%, and the performance of the catalyst was adjusted through temperature regulation.
The excellent performance of sulfur-doped ruthenium oxide catalyst in OER reaction was achieved. In the RDE test, the overpotential of 10mA cm-2 was 268-322mV, which was able to operate continuously and stably for 50 hours, and had a lower overpotential compared to conventional RuO2.
Smart Images

Figure HDA0005189114100000011 
Figure HDA0005189114100000012 
Figure HDA0005189114100000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and particularly relates to a sulfur-doped ruthenium oxide catalyst and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolysis (PEMWE) is a technology that can efficiently produce high-purity hydrogen, but its oxygen evolution reaction (OER) has slow reaction kinetics and is limited by high operating voltage. An increasing number of oxides, hydroxides, nitrogen compounds, organometallics and non-metals have been reported as promising candidates for catalyzing OER in alkaline media. However, the ionic conductivity of the OER reaction in alkaline electrolytes is low, and carbonates are easily accumulated to form pollutants through reactions with carbon dioxide. Under acidic conditions, the ionic conductivity of the OER reaction is high and side reactions are less, however, only a small number of OER catalysts can operate stably in acidic environments.
[0003] Ruthenium (Ru) and iridium (Ir) metals and their oxides are the best performing OER catalysts to date, showing good stability in acidic environments. Although iridium oxide (IrO2) is more stable, ruthenium oxide (RuO2) has better apparent activity and is only one-third the price of Ir. In order to improve the stability and activity of RuO2, a variety of different strategies can be adopted. Among them, the introduction of foreign atoms to reduce the d-band center of Ru and avoid the precipitation of lattice oxygen in the OER reaction has become the key. Sulfur, as a homologous element of oxygen, not only has an electron orbital distribution similar to that of oxygen, but its larger atomic radius can also effectively disperse the electrons on Ru, thereby increasing the activity and stability of Ru-based catalysts. Therefore, how to regulate the precise doping of sulfur has become the key to the performance of the catalyst.
[0004] Therefore, how to quickly and efficiently synthesize high-performance, high-stability sulfur-doped RuO2 with a suitable doping ratio is a key scientific and technological problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a sulfur-doped ruthenium oxide catalyst to solve the problems in the prior art.
[0006] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0007] One of the purposes of the present invention is to protect a sulfur-doped ruthenium oxide catalyst, which comprises ruthenium oxide and sulfur doped in the ruthenium oxide.
[0008] In certain embodiments, the doping rate of sulfur in the sulfur-doped ruthenium oxide catalyst is 0.4 at.%-3 at.%. The sulfur in the sulfur-doped ruthenium oxide catalyst is uniformly distributed in the ruthenium dioxide crystals.
[0009] In certain embodiments, the ruthenium oxide has a crystallinity of 90-99%.
[0010] In certain embodiments, the particle size of the sulfur-doped ruthenium oxide catalyst is 5-11 nm.
[0011] The second object of the present invention is to provide a method for preparing the above-mentioned sulfur-doped ruthenium dioxide catalyst, comprising the following steps:
[0012] S1: mixing a ruthenium source, a sulfur source, an alkali metal salt and a solvent, and drying them to form a precursor;
[0013] S2: heat-treating, washing, and drying the precursor to obtain a sulfur-doped ruthenium oxide catalyst.
[0014] In certain embodiments, the ruthenium source includes one or more of ruthenium trichloride, ruthenium acetylacetonate, and sodium acetate.
[0015] In certain embodiments, the sulfur source includes one or more of thiourea, sodium sulfide, and potassium sulfide.
[0016] In certain embodiments, the alkali metal salt includes one or more of alkali metal nitrates, alkali metal chlorides, and alkali metal sulfates.
[0017] In certain embodiments, the alkali metal salt includes one or more of potassium nitrate, potassium sulfate, potassium chloride, sodium nitrate, sodium chloride, and sodium sulfate.
[0018] In certain embodiments, the solvent is an alcohol solvent.
[0019] In certain embodiments, the alcohol solvent includes one or more of ethanol, ethylene glycol, isopropanol and glycerol.
[0020] In some specific embodiments, the alcohol solvent is preferably ethanol.
[0021] In some embodiments, in some embodiments, the mass ratio of the ruthenium source and the alkali metal salt is: 0.025-0.1:1.
[0022] In certain embodiments, the mass ratio of the ruthenium source to the sulfur source is 1:2-3.5.
[0023] In certain embodiments, the mass volume ratio of the ruthenium source to ethanol is 1-3 mg / mL.
[0024] In certain embodiments, the mixing time is 0.5-3 hours.
[0025] In certain embodiments, the mixing temperature is 20-35°C.
[0026] In certain embodiments, the mixing method includes but is not limited to stirring.
[0027] In certain embodiments, the drying in step S1 is vacuum drying, and the drying conditions are not particularly limited, subject to complete drying. After drying is completed, a precursor is obtained.
[0028] In certain embodiments, the vacuum drying includes rotary evaporation and / or drying; preferably rotary evaporation and drying; firstly, the water in the mixed solution is evaporated by rotary evaporation, and then the evaporated solid is dried to obtain a solid powder.
[0029] In certain embodiments, the temperature of the vacuum rotary evaporation is 45°C-55°C.
[0030] In certain embodiments, the vacuum drying temperature is 60-80°C.
[0031] In certain embodiments, the vacuum drying time is 8-20 hours.
[0032] In certain embodiments, the heat treatment temperature is 350-500°C.
[0033] In certain embodiments, the heat treatment time is 2-3 hours.
[0034] In certain embodiments, the heating rate of the heat treatment is 1-10° C. / min.
[0035] In certain embodiments, the heat treatment is performed in an oxygen atmosphere.
[0036] In certain embodiments, the washing in step S2 comprises washing with deionized water.
[0037] In certain embodiments, the drying condition in step S2 is vacuum drying; the temperature of the vacuum drying is preferably 60-80°C.
[0038] The third object of the present invention is to protect the use of the sulfur-doped ruthenium oxide catalyst as described above in the acidic anode oxygen evolution reaction.
[0039] In certain embodiments, the catalyst is used to activate an anode proton exchange membrane water electrolysis reaction.
[0040] A third object of the present invention is to protect a membrane electrode, which includes the sulfur-doped ruthenium oxide catalyst as described above.
[0041] In certain embodiments, the membrane electrode comprises:
[0042] Proton exchange membrane;
[0043] One side surface of the proton exchange membrane is covered with a cathode catalyst layer, and the other side surface is covered with an anode catalyst layer, and the anode catalyst layer includes the sulfur-doped ruthenium oxide catalyst as described above.
[0044] In certain embodiments, the method for preparing the anode catalyst layer comprises: mixing the sulfur-doped ruthenium oxide catalyst, Nafion solution and a solvent to obtain the anode catalyst layer.
[0045] A third object of the present invention is to protect a water electrolysis device, including the water electrolysis membrane electrode as described above.
[0046] Beneficial effects:
[0047] The invention provides a sulfur-doped ruthenium oxide catalyst, which comprises a ruthenium oxide crystal and sulfur uniformly doped in the ruthenium oxide crystal. The invention introduces sulfur into the ruthenium oxide crystal, so that trace ruthenium-oxygen bonds in the ruthenium oxide crystal are replaced by sulfur, thereby improving the activity of the ruthenium oxide catalyst. The test shows that the sulfur-doped ruthenium oxide catalyst exhibits excellent performance in the OER reaction, and the RDE test shows that the 10 mA cm -2 The overpotential is 268-322mV, with the lowest being only 268mV, and can run stably for 50 hours; it has a lower overpotential than conventional RuO2. Moreover, the preparation method of sulfur-doped ruthenium oxide catalyst is simple, and the sulfur content in the sulfur-doped ruthenium oxide catalyst can be independently controlled by temperature, thereby obtaining different performances. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is the XRD test diagram of the catalyst in Examples 1 to 3 of the present invention.
[0049] Figure 2a This is the XPS fine spectrum of catalyst S in Example 2 of the present invention.
[0050] Figure 2b This is the XPS fine spectrum of the catalyst Ru in Example 2 of the present invention.
[0051] Figure 3 TEM and EDS-Mapping scanning electron microscope images of the catalyst in Example 1.
[0052] Figure 4a This is a test chart of oxygen evolution of the catalysts prepared in Examples 1 to 3 when sulfuric acid is used as the electrolyte.
[0053] Figure 4bThis is a test chart of oxygen evolution of the catalysts prepared in Examples 4 to 5 when sulfuric acid is used as the electrolyte.
[0054] Figure 4c This is a test chart of oxygen evolution of the catalysts prepared in Examples 6 to 7 when sulfuric acid is used as the electrolyte.
[0055] Figure 5 It is the EPR test chart of the catalyst in Examples 1 to 3 of the present invention and Comparative Example 1.
[0056] Figure 6 It is a constant voltage test diagram of the catalyst in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0057] The present invention provides a sulfur-doped ruthenium oxide catalyst, which comprises ruthenium oxide and sulfur doped in the ruthenium oxide; the stability and activity of the ruthenium oxide catalyst are improved by optimizing the doping rate of sulfur in the sulfur-doped ruthenium oxide catalyst; when the doping rate of sulfur in the sulfur-doped ruthenium oxide catalyst is 0.4at.%-3at.%, the doping rate is atomic percentage, which refers to the ratio of the number of sulfur atoms to the total number of catalyst atoms; the relative atomic percentage is characterized by XPS.
[0058] The sulfur-doped ruthenium oxide catalyst showed excellent performance in the OER (oxygen evolution reaction), with a RDE test (including oxygen evolution and constant voltage) of 10 mA cm -2 The overpotential is only 268 mV, and the catalyst can be operated stably for 50 hours. The sulfur doping rate in the sulfur-doped ruthenium oxide catalyst can also be 0.5 at.%-2.5 at.%, 1 at.%-2 at.%, or 1.2 at.%-1.6 at.%, preferably 1.34 at.%.
[0059] In certain embodiments, the crystallinity of the ruthenium oxide is 90-99%, 91-98%, 92-96%, 93-95%, and preferably 93.6%.
[0060] In certain embodiments, the particle size of the sulfur-doped ruthenium oxide catalyst is 5-11 nm, or 6-8 nm, or 5 nm, 6 nm, 7 nm, 7.5 nm, 8 nm, 9 nm, 10 nm, or 11 nm; preferably, it is 7.5 nm.
[0061] The present invention also provides a method for preparing the above-mentioned sulfur-doped ruthenium dioxide catalyst, comprising the following steps:
[0062] S1: mixing a ruthenium source, a sulfur source, an alkali metal salt and a solvent, and drying them to form a precursor;
[0063] S2: heat-treating, washing, and drying the precursor to obtain a sulfur-doped ruthenium oxide catalyst.
[0064] In the present invention, a ruthenium source, a sulfur source, and an alkali metal salt are firstly put into a mortar and ground and mixed evenly to form a precursor 1, and then a solvent is added to the precursor 1, stirred and mixed to obtain a mixed liquid, and then the mixed liquid is dried to obtain a precursor 2; the precursor 2 is evenly put into a mortar and sintered at a high temperature, and the sintered product is poured out, washed with deionized water for multiple times, and then dried to obtain a sulfur-doped ruthenium dioxide catalyst.
[0065] In certain embodiments, the ruthenium source includes one or more of ruthenium trichloride, ruthenium acetylacetonate, and ruthenium acetate.
[0066] In certain embodiments, the sulfur source includes one or more of thiourea, sodium sulfide, and potassium sulfide.
[0067] In some embodiments, the sulfur source is thiourea.
[0068] In certain embodiments, the alkali metal salt comprises one or more of alkali metal nitrates, alkali metal chlorides, and alkali metal sulfates.
[0069] In certain embodiments, the alkali metal salt includes one or more of potassium nitrate, potassium sulfate, potassium chloride, sodium nitrate, sodium chloride, and sodium sulfate.
[0070] In some embodiments, the alkali metal salt is sodium nitrate.
[0071] In certain embodiments, the solvent is an alcohol solvent.
[0072] In certain embodiments, the alcohol solvent includes one or more of ethanol, ethylene glycol, and isopropanol.
[0073] In some embodiments, the alcohol solvent is ethanol.
[0074] In some embodiments, the mass ratio of the ruthenium source to the alkali metal salt is 0.025-0.1:1; it can also be 0.035-0.05:1; it can also be a value in any range, such as 0.025:1, 0.035:1, 0.05:1, 0.075:1, 0.1:1. The alkali metal salt is added to provide an oxidizing atmosphere to oxidize the ruthenium in the ruthenium source to ruthenium dioxide. If the amount of alkali metal salt is too high, it will be difficult to remove it later, and if it is too low, the precursor will not be completely converted into RuO2.
[0075] In some embodiments, the mass ratio of the ruthenium source to the sulfur source is: 1:2-3.5; it can also be 1:2.3-3.2; it can also be 1:2.405-3.126; it can also be a value within any range, for example 1:2, 1:2.2, 1:2.405, 1:2.5, 1:2.7, 1:3, 1:3.125, 1:3.3, 1:3.5.
[0076] In certain embodiments, the mass volume ratio of the ruthenium source to ethanol is 1-3 mg / mL; it can also be 1-2 mg / mL, it can also be 2-3 mg / mL, or it can be a value within any range, such as 1, 1.4, 1.5, 2, 2.5, 3 mg / mL; if the mass volume ratio is too high or too low, the degree of sulfur doping will be affected.
[0077] In certain embodiments, the mixing time is 0.5-3 h; it can also be 0.5-2 h, it can also be 1-2 h, or it can be a value within any range, such as 0.5, 1, 1.5, 2, 2.5, 3 h.
[0078] In certain embodiments, the mixing temperature is 20-35°C; it can also be 22-33°C, or 25-30°C; it can also be a value within any range, such as 20°C, 25°C, 28°C, 30°C, or 32°C.
[0079] In certain embodiments, the mixing method includes but is not limited to stirring.
[0080] In certain embodiments, the drying in step S1 is vacuum drying, and the drying conditions are not particularly limited, subject to complete drying. After drying is completed, a precursor is obtained.
[0081] In certain embodiments, the vacuum drying includes rotary evaporation and / or drying; preferably rotary evaporation and drying; firstly, the water in the mixed solution is evaporated by rotary evaporation, and then the evaporated solid is dried to obtain a solid powder.
[0082] In certain embodiments, the temperature of the vacuum rotary evaporation is 45-55°C.
[0083] In certain embodiments, the temperature of the vacuum drying is 60-80°C; it can also be 60-70°C, or a value within any range, such as 60°C, 70°C, or 80°C.
[0084] In certain embodiments, the vacuum drying time is 8-20 h; it can also be 10-18 h, or 12-16 h, or a value within any range, such as 10 h, 12 h, 14 h, 16 h, or 18 h.
[0085] In certain embodiments, the heat treatment temperature is 350-500°C; it can also be 400-500°C, it can also be 420-450°C, it can also be a value in any range, for example, 350°C, 400°C, 425°C, 450°C, 480°C; preferably 425°C.
[0086] In certain embodiments, the heat treatment time is 2-3 hours; it can also be a value within any range, such as 2h, 2.5h, 3h.
[0087] In some embodiments, the heat treatment is to heat the temperature from room temperature to the sintering temperature and then keep it warm, and the heating rate is 1-10°C / min; it can also be 2-8°C / min, or 4-6°C / min; it can also be a value within any range, such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10°C / min.
[0088] Specifically, the sintering temperature will affect the crystallinity of the prepared catalyst. The higher the sintering temperature, the lower the sulfur content of the prepared catalyst is, and the catalyst cannot be effectively regulated. The lower the sintering temperature, the more free sulfur there is in the catalyst, which affects the reaction activity of OER. The sulfur content in the sulfur-doped ruthenium dioxide catalyst can be adjusted by adjusting the sintering temperature, thereby obtaining sulfur-doped ruthenium dioxide catalysts with different performances. Therefore, based on a variety of other influencing factors and after a lot of creative work, it was concluded that the heat treatment effect on the catalyst is best when the heating rate is 1-10°C / min, the temperature is 350-500°C, and the time is 2-3h.
[0089] In some embodiments, the heat treatment is performed in an oxygen atmosphere, such as an air atmosphere.
[0090] In certain embodiments, the washing in step S2 includes washing with deionized water to remove the metal salt.
[0091] In certain embodiments, the drying condition in step S2 is vacuum drying.
[0092] In certain embodiments, the temperature of the vacuum drying is 60-80°C; it can also be 60-70°C, or a value within any range, such as 60°C, 70°C, or 80°C.
[0093] The preparation method of the sulfur-doped ruthenium oxide catalyst provided by the present invention is simple and suitable for industrial large-scale production, laying a foundation for the large-scale preparation of stable and highly active proton exchange membrane water electrolysis anode catalysts. The method introduces sulfur into ruthenium oxide, controls the sulfur content in the catalyst by temperature control, and improves the activity of the catalyst.
[0094] The sulfur-doped ruthenium oxide catalyst was characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy and elemental mapping (TEM and EDS-Mapping scanning electron microscopy). Figure 1 is the XRD spectrum of Example 1-3, Figure 2a-2b is the XPS fine spectrum of Example 1, Figure 3 TEM and EDS-Mapping spectra. The characterization results show that the sulfur-doped ruthenium dioxide catalyst prepared by this method has sulfur uniformly doped into ruthenium dioxide.
[0095] The present invention also relates to the use of the sulfur-doped ruthenium oxide catalyst as described above in an acidic anode oxygen evolution reaction; wherein the catalyst is used to activate the anode proton exchange membrane water electrolysis reaction.
[0096] The present invention also protects a membrane electrode, which comprises the sulfur-doped ruthenium oxide catalyst as described above.
[0097] In certain embodiments, the membrane electrode comprises:
[0098] Proton exchange membrane;
[0099] One side surface of the proton exchange membrane is covered with a cathode catalyst layer, and the other side surface is covered with an anode catalyst layer, and the anode catalyst layer includes the sulfur-doped ruthenium oxide catalyst as described above.
[0100] In certain embodiments, the proton exchange membrane includes but is not limited to a Nafion membrane.
[0101] In certain embodiments, the method for preparing the anode catalyst layer comprises: mixing the sulfur-doped ruthenium oxide catalyst, Nafion solution and a solvent to obtain the anode catalyst layer.
[0102] In certain embodiments, the solvent includes, but is not limited to, water, ethanol, or isopropanol.
[0103] The present invention also includes a water electrolysis device, comprising the water electrolysis membrane electrode as described above.
[0104] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0105] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0106] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0107] Example 1
[0108] The raw materials described in this example were all purchased commercially.
[0109] Take 100 mg of ruthenium trichloride, 240.5 mg of thiourea and 2 g of sodium nitrate in a mortar, grind the mixture for 30 minutes until it is powdery, place it in a 100 mL beaker, add 50 mL of ethanol and a stirrer, stir at 25 ° C for 1.5 hours, transfer the resulting solution to a round-bottom flask, and perform vacuum rotary evaporation in a water bath at a temperature of 50 ° C. Collect the remaining solid in a 25 mL beaker and dry it in a vacuum oven at 60 ° C overnight.
[0110] The dried mixture is placed in a corundum porcelain boat, which is then transferred to a tubular furnace for high-temperature sintering. The high-temperature sintering conditions are heat treatment at 425°C in an air atmosphere for 180 minutes (heating rate 2°C / min), followed by natural cooling, filtration and washing three times with deionized water, and vacuum drying at 60°C to obtain sulfur-doped ruthenium dioxide.
[0111] See also Figure 1 , Figure 2a , Figure 2b and Figure 3, which are respectively the XRD test pattern of the sulfur-doped ruthenium dioxide catalyst prepared in Example 1 of the present invention, the XPS fine spectrum of the sulfur-doped ruthenium dioxide catalyst S, the XPS fine spectrum and the electron microscope image of the sulfur-doped ruthenium dioxide catalyst Ru. It can be seen that the sulfur-doped ruthenium dioxide catalyst is successfully prepared in this example, wherein the sulfur atom doping rate in the sulfur-doped ruthenium dioxide is 1.34at.%, the particle size is about 7.5nm, and the crystallinity of ruthenium dioxide is 93.6%.
[0112] Example 2
[0113] The difference from Example 1 is that the sintering temperature in the tube furnace is 400° C., and the other conditions are the same as those in Example 1.
[0114] See also Figure 1 The XRD test diagram of the sulfur-doped ruthenium dioxide catalyst prepared in Example 2 shows that the sulfur-doped ruthenium dioxide catalyst was successfully prepared in this example, wherein the sulfur atom doping rate in the sulfur-doped ruthenium dioxide was 1.96 at.%, the particle size was about 6.9 nm, and the crystallinity of ruthenium dioxide was 90.4%.
[0115] Example 3
[0116] The difference from Example 1 is that the sintering temperature in the tube furnace is 450° C., and the other conditions are the same as those in Example 1.
[0117] See also Figure 1 From the XRD test diagram of the catalyst prepared in Example 3, it can be seen that the sulfur-doped ruthenium dioxide catalyst was successfully prepared in this example. The sulfur-doped ruthenium dioxide catalyst had a sulfur atom doping rate of 0.41 at.%, a particle size of about 8.9 nm, and a ruthenium dioxide crystallinity of 98.8%.
[0118] Example 4
[0119] Take 70 mg of ruthenium trichloride, 240.5 mg of thiourea and 2 g of sodium nitrate in a mortar, grind the mixture thoroughly for 30 minutes until it is powdery. After grinding, place it in a 100 mL beaker, add 50 mL of ethanol and a stirrer, stir at 25 ° C for 1 hour, transfer the resulting solution to a round-bottom flask, and perform vacuum rotary evaporation in a water bath at a temperature of 50 ° C. Collect the remaining solid in a 25 mL beaker and place it in a vacuum oven at 60 ° C to dry overnight.
[0120] The dried mixture is placed in a corundum porcelain boat, and then the corundum porcelain boat is transferred to a tubular furnace for high-temperature sintering. The high-temperature sintering conditions are heat treatment at 400°C in an air atmosphere for 180 minutes (heating rate 2°C / min), followed by natural cooling, filtration and washing three times with deionized water, and vacuum drying at 60°C to obtain sulfur-doped ruthenium dioxide.
[0121] The sulfur-doped ruthenium dioxide catalyst prepared in this example was tested to have a sulfur atom doping rate of 1.87 at.%, a particle size of about 6.8 nm, and a ruthenium dioxide crystallinity of 95.7%.
[0122] Example 5
[0123] The difference from Example 4 is that the sintering temperature in the tube furnace is 450° C., and the other conditions are the same as those in Example 4.
[0124] The sulfur-doped ruthenium dioxide catalyst prepared in this example was tested to have a sulfur atom doping rate of 0.4 at.%, a particle size of about 9.7 nm, and a ruthenium dioxide crystallinity of 97.6%.
[0125] Example 6
[0126] Take 100 mg of ruthenium trichloride, 312.6 mg of thiourea and 2 g of sodium nitrate in a mortar, grind the mixture thoroughly for 30 minutes until it is in powder form, place it in a 100 mL beaker after grinding, add 50 mL of ethanol and a stirrer, stir at 25 ° C for 2 hours, transfer the resulting solution to a round-bottom flask, and perform vacuum rotary evaporation in a water bath at a temperature of 50 ° C. Collect the remaining solid in a 25 mL beaker and place it in a vacuum oven at 60 ° C to dry overnight.
[0127] The dried mixture is placed in a corundum porcelain boat, which is then transferred to a tubular furnace for high-temperature sintering. The high-temperature sintering conditions are heat treatment at 400°C in an air atmosphere for 180 minutes (heating rate 2°C / min), followed by natural cooling, filtration and washing three times with deionized water, and vacuum drying at 60°C to obtain sulfur-doped ruthenium dioxide.
[0128] The sulfur-doped ruthenium dioxide catalyst prepared in this example was tested to have a sulfur atom doping rate of 2.85 at.%, a particle size of about 7.3 nm, and a ruthenium dioxide crystallinity of 92.4%.
[0129] Example 7
[0130] The difference from Example 6 is that the sintering temperature in the tube furnace is 450° C., and the other conditions are the same as those of Example 6.
[0131] It was detected that the sulfur-doped ruthenium dioxide catalyst prepared in this example had a sulfur doping rate of 0.52 at.%, a particle size of about 10.4 nm, and a ruthenium dioxide crystallinity of 97.8%.
[0132] Comparative Example 1
[0133] The preparation method is the same as that of Example 1, except that thiourea is not added to prepare the RuO2 catalyst.
[0134] XPS test was performed on RuO2, and XPS characterization showed that the sulfur content of the RuO2 catalyst was between 0.15at.% and 0.21at.%. Although no sulfur source was introduced, trace sulfur elements would be detected in the air during the XPS test. For example, part of the sulfur in the air is adsorbed on the surface of the RuO2 catalyst after sintering. Therefore, trace sulfur elements would be detected in the XPS test.
[0135] Effect test example:
[0136] The catalysts prepared in Examples 1 to 7 were subjected to oxygen evolution test, EPR test and constant voltage test, and RuO2 in Comparative Example 1 was used as a control; wherein the overpotential of RuO2 in Comparative Example 1 was about 351 mV, and it operated stably for 10 hours.
[0137] 1. Oxygen evolution reaction (OER) test method: The samples were tested using a CHI760E electrochemical workstation at 25°C. Using sulfuric acid (0.5 mol / L) as the electrolyte, the prepared catalyst dispersion (mixed at a ratio of 3 mg catalyst, 1 mL ethanol and 10 μL nafion) was evenly dropped on the glass / carbon electrode and allowed to dry naturally. The calomel reference electrode and the counter electrode were assembled to the corresponding positions in the measuring cup, placed in the electrolyte, and the sample was tested for oxygen evolution. The theoretical overpotential of OER at the reversible hydrogen standard electrode is 1.23 V, 10 mA cm -2 The catalyst under test was tested at 10 mA cm -2 The voltage at the current density is then subtracted from 1.23 to obtain the overpotential of the catalyst to be tested.
[0138] 2. EPR test: Use A300 electron paramagnetic resonance spectrometer to perform single electron paramagnetic resonance test on the sample.
[0139] 3. Constant voltage test: The samples were tested using a CHI760E electrochemical workstation at 25°C. Sulfuric acid (0.5 mol / L) was used as the electrolyte, and the prepared catalyst dispersion (mixed in a ratio of 3 mg catalyst, 1 mL ethanol and 10 μL nafion) was evenly dropped on the microporous carbon paper, the carbon paper was fixed on the working electrode, and the calomel reference electrode and the counter electrode were assembled to the corresponding positions in the measuring cup, placed in the electrolyte, and a constant voltage (1.605 V) stability test was performed.
[0140] The test results are as follows:
[0141] Figure 4a This is the RDE oxygen evolution test diagram of the sulfur-doped ruthenium dioxide catalyst prepared in Example 1-3. Figure 4bThis is the RDE oxygen evolution test diagram of the sulfur-doped ruthenium dioxide catalyst prepared in Example 4-5. Figure 4c This is the RDE oxygen evolution test chart of the sulfur-doped ruthenium dioxide catalyst prepared in Example 6-7. Figure 5 This is an EPR test graph of the sulfur-doped ruthenium dioxide catalyst obtained in Examples 1 to 3 and the RuO2 in Comparative Example 1; Figure 6 This is the RDE constant voltage test diagram of the catalyst prepared in Example 1.
[0142] Figure 5 It is an EPR comparison sample test chart of Examples 1-3 and the control sample RuO2 catalyst. EPR tests the oxygen vacancy concentration in the sample. The larger the amplitude, the higher the oxygen vacancy concentration. Among them, the sample at 400°C has the largest amplitude, indicating the highest oxygen vacancy concentration, and the sample at 450°C has the smallest amplitude, indicating the lowest oxygen vacancy concentration. Since the sample is doped with sulfur to replace the oxygen in the sample, it can be considered that the sulfur concentration is proportional to the oxygen vacancy concentration, indicating that the lower the heat treatment temperature, the higher the doping degree of the sample. The sulfur content result of XPS also illustrates this point. The present invention also adjusts the sulfur doping degree through heat treatment conditions.
[0143] Figure 4a-4c The RDE oxygen evolution test graphs of the sulfur-doped ruthenium dioxide catalysts prepared in Examples 1 to 7 are shown; it can be seen that at 10 mA cm -2 At a current density of 10 mA cm, the overpotentials of the sulfur-doped ruthenium dioxide catalysts prepared in Examples 1 to 7 were 268-322 mV, among which Example 1 had the highest apparent activity. -2 The lower overpotential is only 268mV.
[0144] Figure 6 The constant voltage test also shows that Example 1 can operate stably for more than 50 hours, indicating that the activity and stability of Example 1 are higher than those of the RuO2 catalyst in Comparative Example 1 without the introduction of a sulfur source.
[0145] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A sulfur-doped ruthenium oxide catalyst, characterized in that: The sulfur-doped ruthenium oxide catalyst comprises ruthenium oxide and sulfur doped in the ruthenium oxide; the doping rate of sulfur in the sulfur-doped ruthenium oxide catalyst is 0.4 at.%-3 at.%.
2. The sulfur-doped ruthenium oxide catalyst according to claim 1, characterized in that The crystallinity of the ruthenium oxide is 90-99%; preferably, the particle size of the sulfur-doped ruthenium oxide catalyst is 5-11 nm.
3. The method for preparing the sulfur-doped ruthenium oxide catalyst according to claim 1 or 2, comprising the following steps: S1: mixing a ruthenium source, a sulfur source, an alkali metal salt and a solvent, and drying them to form a precursor; S2: heat-treating, washing, and drying the precursor to obtain a sulfur-doped ruthenium oxide catalyst.
4. The preparation method according to claim 3, characterized in that: The ruthenium source includes one or more of ruthenium trichloride, ruthenium acetylacetonate and ruthenium acetate; Preferably, the sulfur source includes one or more of thiourea, sodium sulfide and potassium sulfide; Preferably, the mass ratio of the ruthenium source to the sulfur source is 1:2-3.
5.
5. The preparation method according to claim 3, characterized in that: The alkali metal salt includes one or more of alkali metal nitrates, alkali metal chlorides, and alkali metal sulfates; Preferably, the mass ratio of the ruthenium source to the alkali metal salt is 0.025-0.1:
1.
6. The preparation method according to claim 3, characterized in that: The solvent is an alcohol solvent; Preferably, the alcohol solvent includes one or more of ethanol, ethylene glycol, isopropanol and glycerol; Preferably, the mass volume ratio of the ruthenium source to ethanol is 1-3 mg / mL.
7. The preparation method according to claim 3, characterized in that: The heat treatment temperature is 350-500° C.; and / or, the heat treatment time is 2-3 hours; and / or, the heat treatment is performed in an oxygen atmosphere.
8. Use of the sulfur-doped ruthenium oxide catalyst according to any one of claims 1 to 2 or the sulfur-doped ruthenium oxide catalyst prepared by the preparation method according to any one of claims 3 to 7 in an acidic anode oxygen precipitation reaction.
9. A membrane electrode, characterized in that: The membrane electrode comprises the sulfur-doped ruthenium oxide catalyst described in any one of claims 1-2 or the sulfur-doped ruthenium oxide catalyst prepared by the preparation method described in any one of claims 3-7.
10. A water electrolysis device, characterized in that: It comprises the sulfur-doped ruthenium oxide catalyst described in any one of claims 1-2, or the sulfur-doped ruthenium oxide catalyst prepared by the preparation method described in any one of claims 3-7, or the membrane electrode described in claim 9.
Citation Information
Patent Citations
IrO2 / S catalyst, membrane electrode and preparation method and application of IrO2 / S catalyst and membrane electrode
CN118186470A
Preparation Method and Application of Non-noble Metal Single Atom Catalyst
US20220042184A1
Cited By
Anion-doped ruthenium oxide bifunctional catalyst as well as preparation method and application thereof
CN121826781A